GABA concentration in sensorimotor cortex following high‐intensity exercise and relationship to lactate levels. (27th December 2017) - Coxon, James P.; Cash, Robin F. H.; Hendrikse, Joshua J.; Rogasch, Nigel C.; Stavrinos, Ellen; Suo, Chao; Yücel, Murat
Abstract : Key points: Magnetic resonance spectroscopy was conducted before and after high‐intensity interval exercise. Sensorimotor cortex GABA concentration increased by 20%. The increase was positively correlated with the increase in blood lactate. There was no change in dorsolateral prefrontal cortex. There were no changes in the glutamate‐glutamine‐glutathione peak. Abstract: High‐intensity exercise increases the concentration of circulating lactate. Cortical uptake of blood borne lactate increases during and after exercise; however, the potential relationship with changes in the concentration of neurometabolites remains unclear. Although changes in neurometabolite concentration have previously been demonstrated in primary visual cortex after exercise, it remains unknown whether these changes extend to regions such as the sensorimotor cortex (SM) or executive regions such as the dorsolateral prefrontal cortex (DLPFC). In the present study, we explored the acute after‐effects of high‐intensity interval training (HIIT) on the concentration of gamma‐Aminobutyric acid (GABA) and the combined glutamate–glutamine–glutathione (Glx) spectral peak in the SM and DLPFC, as well as the relationship with blood lactate levels. Following HIIT, there was a robust increase in GABA concentration in the SM, as evident across the majority of participants. This change was not observed in the DLPFC. Furthermore, the increase in SM GABA was positively correlated with an increase in blood lactate. There were no changes in Glx concentration in either region. The observed increase in SM GABA concentration implies functional relevance, whereas the correlation with lactate levels may relate to the metabolic fate of exercise‐derived lactate that crosses the blood–brain barrier. Key points: Magnetic resonance spectroscopy was conducted before and after high‐intensity interval exercise. Sensorimotor cortex GABA concentration increased by 20%. The increase was positively correlated with the increase in blood lactate. There was no change in dorsolateral prefrontal cortex. There were no changes in the glutamate‐glutamine‐glutathione peak.